Membangun Kesadaran Sosial Melalui Pembelajaran IPS yang Interaktif - Putri, Salisah; Siregar, Putri Darnisah; Andini, Ayu; Novia, Nurul Yogi; Hasibuan, Siti Marhamah; Yusnaldi, Eka (Pusdikra-Publishing.com, 2024)
Social Studies Education (IPS) plays an important role in shaping students' character, particularly in developing social awareness. IPS learning not only teaches social knowledge but also actively engages students to understand and respond to existing social issues. One of the major challenges in IPS education is connecting theory with the reality of students' lives, which is often perceived as too abstract. Therefore, an interactive learning approach is essential to increase student engagement, develop critical thinking skills, and build empathy. Learning that emphasizes interactivity, such as group discussions, role-playing, and the use of digital media, can help students apply knowledge in everyday life and strengthen their social awareness. Through literature review, this study aims to explore interactive methods in IPS learning that can enhance students' social awareness. The results show that interaction-based learning can improve student participation, social skills, and understanding of existing social issues, which in turn supports the development of a more socially conscious student character.